Pemberdayaan UMKM melalui Tradisi Panjang Mulud dalam Pengembangan Ekonomi Kreatif Berbasis Kearifan Lokal - Ubay Haki; Eka Danik Prahastiwi (Lembaga Yasin AlSys, 2026)
Although local traditions have strategic potential as a source for creative economy development, the utilization of the Panjang Mulud tradition in Sukaindah Village, Baros Subdistrict, Serang Regency still tends to be ceremonial and has not been optimized as an instrument for economic empowerment based on local wisdom. This study aims to analyze the potential of the Panjang Mulud tradition in empowering micro, small, and medium enterprises (MSMEs) and to formulate a creative economy development model based on local wisdom. This study used a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation involving MSME actors, community leaders, and village officials selected through purposive sampling. The data were analyzed using the Miles, Huberman, and Saldaña model through the stages of data condensation, data display, and conclusion drawing and verification. The results show that the Panjang Mulud tradition has economic potential that can encourage MSME activities through product innovation, strengthening human resource capacity, digitalizing marketing, and collaboration among stakeholders. However, the optimization of this potential still faces obstacles in the form of limited innovation, low digital literacy, and the absence of sustainable empowerment programs. These findings offer a local tradition-based MSME empowerment model as a conceptual contribution to the development of a creative economy based on local wisdom. Practically, the results of this study can serve as a reference for local governments and communities in designing sustainable MSME empowerment strategies through the optimization of local cultural potential.